2011
DOI: 10.1007/s11010-011-0930-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyperhomocysteinemia induces oxidative damage in the rat lung

Abstract: Tissue accumulation of homocysteine occurs in classical homocystinuria, a metabolic disease characterized biochemically by cystathionine β-synthase deficiency. Vascular manifestations such as myocardial infarction, cerebral thrombosis, hepatic steatosis, and pulmonary embolism are common in this disease and poorly understood. In this study, we investigated the effect of chronic hyperhomocysteinemia on some parameters of oxidative stress (thiobarbituric acid-reactive substances, protein carbonyl content, 2',7'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…We verified that in the OVA group there was a decrease in CAT and GPx activities, but there was not an alteration in SOD, suggesting an unbalance in oxidant‐antioxidant status. SOD promotes the dismutation of superoxide, and CAT and GPx induce the reduction of hydrogen peroxide (Cunha et al, ). We suggested that an increase in ROS formation did not increase the consumption of the SOD that induces the dismutation of superoxide in hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…We verified that in the OVA group there was a decrease in CAT and GPx activities, but there was not an alteration in SOD, suggesting an unbalance in oxidant‐antioxidant status. SOD promotes the dismutation of superoxide, and CAT and GPx induce the reduction of hydrogen peroxide (Cunha et al, ). We suggested that an increase in ROS formation did not increase the consumption of the SOD that induces the dismutation of superoxide in hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…2007; da Cunha et al. 2011). The increase in oxidative stress has been suggested as a link between HHcy and many CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these latter pathologies display a perturbation of transition metal homeostasis and a deregulation of the enzymatic and chemical antioxidant systems. In particular, patients or animals bearing tumours, or animal models of chronic hyperhomocystinemia exhibit a dysfunctional catalase bioactivity12131415161718.…”
mentioning
confidence: 99%